Green Malt for a Green Future – Feasibility and Challenges of Brewing Using Freshly Germinated (Unkilned) Malt: A Review. (2nd October 2021) - Dugulin, Celina A.; De Rouck, Gert; Cook, David J.
Abstract: In malting, the kilning step is by far the dominant user of energy and has, thus, become the main target in reducing the carbon footprint of malting operations. Brewing beer using "green" (germinated, but not dried) malt, thus, saving the substantial energy input associated with kilning and conserving the water contained in the green malt, could improve the energy and water efficiency of malting operations. Furthermore, the high enzyme complement in green malt could enable more efficient brewing using unmalted cereals (e.g., raw barley) to create highly attenuated beers, without the use of exogenous enzymes. The objective of this review is to unravel the major advantages, but also quality and technical challenges, which could serve as a base for future studies on successfully brewing with green malt. Furthermore, the aim is to evaluate the impacts of such a process on beer flavor and flavor (in)stability. This is important to establish because one can make arguments that such a process will either improve flavor stability (reduced heat load should reduce the pool of staling aldehydes) or worsen it (since lipoxygenase activity and dimethyl sulphide potential can be regulated by heat treatment during kilning).